Analisis Potensi Likuifaksi Berdasarkan Data SPT Di Kulon Progo Yogyakarta - Nova, Septi Devita; Fatnanta, Ferry; Yusa, Muhamad (Dept. of Civil Engineering Universitas Riau, 2023)
Liquefaction is a process of changing soil properties when the solid state becomes liquid caused by cyclic loads as a result of an earthquake so that the pore water pressure increases, approaching and even exceeding the magnitude of the total pressure. Liquefaction occurs due to earthquakes that occur in the area. Tectonic earthquake is one type of earthquake that can trigger liquefaction. The purpose of this study was to examine the potential for liquefaction in Kulon Progo Yogyakarta as the location of the New Yogyakarta International Airport, analyze the safety score (FS), and the value of the liquefaction potential index (LPI). The method used is the Idriss – Boulanger (2014) method using SPT data which is tested at three test points, namely BH-01, BH-03, and BH-06. For this study earthquake data were obtained from the USGS site and the 2017 Earthquake Hazard Map with variations in the earthquake magnitude used were 5.00; 6.30; and 8.10 and ground acceleration data using a probability of 7% in 75 years with a return period of 1000 years. Soil classification based on USCS shows that the soil at the study site is poorly graded sand which contains little fine grain. The results of the study indicate that the research location is prone to liquefaction. Liquefaction occurs at each test point at depth of 4.00 m and 6,00 m, especially at Mw 8.1 and amax 0,48 g with variation where soil resistance is low. Then, based on the classification of the liquefaction potential index numbers which are in the low to high range and the estimated decrease that occurs is up to 23,6 cm.